Hardening composition

The curable composition, featuring a soluble maleimide-containing monomer and an acrylate monomer, addresses the limitations of existing inkjet adaptive planarization materials by providing a cured layer with superior mechanical strength, thermal stability, and etch resistance.

JP7663515B2Active Publication Date: 2025-04-16CANON KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021573142
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-06
Filing Date
2020-07-13
Publication Date
2025-04-16
Estimated Expiration
2040-07-13

AI Technical Summary

Technical Problem

Existing curable compositions for inkjet adaptive planarization lack high etch resistance, mechanical strength, and thermal stability, which are essential for advanced substrate processing.

Method used

A curable composition comprising a first monomer and a second monomer, where the second monomer contains a ring structure such as a maleimide ring, is soluble in the first monomer, and has a viscosity of 10 mPa·s or less, forming an acrylate/maleimide copolymer with enhanced properties.

Benefits of technology

The curable composition achieves fast curing speeds, high thermal stability, good mechanical strength, and high etch resistance, with a cured layer exhibiting a storage modulus of at least 4.5 GPa and a weight loss of 2.5% or less after heat treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663515000005
    Figure 0007663515000005
  • Figure 0007663515000006
    Figure 0007663515000006
  • Figure 0007663515000001
    Figure 0007663515000001
Patent Text Reader

Abstract

The curable composition can include a polymerizable material and an initiator. The polymerizable material can include a first monomer and a second monomer, where the second monomer is soluble in the first monomer and includes a ring structure selected from a maleimide ring, a pyrone ring, or a 2-furanone ring. The curable composition can have a viscosity of 10 mPa·s or less, a fast curing rate, and low shrinkage during curing, making it suitable for use in inkjet-compatible planarization.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Field of Disclosure The present disclosure relates to curable compositions, particularly curable compositions for inkjet compatible planarization. [Background technology]

[0002] Inkjet Adaptive Planarization (IAP) is a process of planarizing the surface of a substrate, such as a wafer containing electronic circuitry, by jetting droplets of a curable composition onto the surface of the substrate and directly contacting a planar superstrate with the applied liquid to form a planar liquid layer. The planar liquid layer is typically solidified under UV light exposure, resulting in a planar surface that can undergo subsequent processing steps, such as baking, etching, and / or further deposition steps, after removal of the superstrate. A need exists for improved IAP materials that result in planar cured layers with high etch resistance, high mechanical strength, and good thermal stability. Summary of the Invention

[0003] In one embodiment, the curable composition can include a polymerizable material and an initiator, the polymerizable material including a first monomer and a second monomer, wherein the second monomer includes a ring structure selected from a maleimide ring, a pyrone ring, or a 2-furanone ring, and the second monomer is soluble in the first monomer and has a viscosity of 10 mPa·s or less.

[0004] In one embodiment, the amount of the second monomer can be up to 2% and 20% by weight, based on the total weight of the curable composition.

[0005] In certain embodiments, the second monomer of the polymerizable material comprises a maleimide ring structure. In one aspect, the second monomer comprises N-benzylmaleimide (N-BMI), N-cyclohexylmaleimide (N-CMI), N-phenylmaleimide (N-PMI), bis(3-ethyl-5-methyl-4-maleimidophenyl)methane (BEMMI), or any combination thereof.

[0006] In further embodiments, the first monomer of the polymerizable material can include an acrylate-monomer. In one embodiment, the acrylate monomer can include an aromatic group. In certain embodiments, the acrylate monomer includes benzyl acrylate (BA), 1-naphthyl acrylate (1-NA), bisphenol A dimethacrylate (BPADMA), or any combination thereof.

[0007] In another embodiment, the polymerizable material of the curable composition can include at least one additional monomer in addition to the first and second monomers. In one aspect, the at least one additional monomer can include substituted or unsubstituted divinylbenzene (DVB).

[0008] In certain embodiments, the polymerizable materials of the curable compositions of the present disclosure can include aromatic acrylate monomers, monomers containing a maleimide ring, and substituted or unsubstituted divinylbenzene (DVB).

[0009] In one embodiment, the curable composition can be essentially free of non-polymerizable solvents.

[0010] In another embodiment of the present disclosure, a laminate can include a substrate and a cured layer overlying the substrate, wherein the cured layer comprises an acrylate / maleimide copolymer, wherein the cured layer has a total carbon content of at least 74%, and wherein the cured layer has a weight loss of 2.5% or less after heat treatment at a temperature of 250° C. for 90 seconds relative to the total weight of the cured layer prior to the heat treatment.

[0011] In one embodiment, the stiffening layer of the laminate can have an average storage modulus of at least 4.5 GPa.

[0012] In another embodiment, the acrylate / maleimide copolymer included in the cured layer of the laminate can further include divinylbenzene.

[0013] In yet another embodiment, a method of forming an article can include applying a layer of a curable composition onto a substrate, wherein the curable composition includes a polymerizable material and a photoinitiator, the polymerizable material includes a first monomer and a second monomer, the second monomer includes a ring structure selected from a maleimide ring, a pyrone ring, or a 2-furanone ring, the second monomer is soluble in the first monomer, and the viscosity of the curable composition is 10 mPa·s or less. The method can also include contacting the curable composition with a superstrate, curing the curable composition with light or heat to form a cured layer, removing the superstrate from the cured layer, and treating the substrate with the cured layer to produce the article.

[0014] In one embodiment of the method, the curing can include at least 65% conversion of all double bonds contained in the polymerizable material within 10 seconds.

[0015] In another embodiment of the method, the polymerizable material of the curable composition can include an acrylate monomer as the first monomer and a monomer containing a maleimide ring as the second monomer. In a further embodiment, the polymerizable material can include at least one additional monomer. In a particular embodiment, the at least one additional monomer can be substituted or unsubstituted divinylbenzene.

[0016] In yet another aspect of the method, the cured layer can have a weight loss of 2.5% or less of the total weight of said cured layer after heat treatment at a temperature of 250° C. for 90 seconds.

[0017] Embodiments are illustrated by way of example and not limitation in the accompanying figures.

[0018] Those skilled in the art will appreciate that elements in the figures are illustrated for simplicity and clarity and have not necessarily been drawn to scale - for example, the dimensions of some of the elements in the figures may be exaggerated relative to other elements to help improve understanding of embodiments of the present invention. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 includes a graph showing the percentage of C═C double bond conversion after 100 seconds of cure at different light intensities, according to an embodiment. [Diagram 2] FIG. 2 includes a graph illustrating the percentage of C═C double bond conversion with increasing cure time, according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Detailed Description The following description is provided to aid in understanding the teachings disclosed herein and focuses on specific embodiments and implementations of the teachings. This focus is provided to aid in describing the teachings and should not be construed as a limitation on the scope or applicability of the teachings.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs.Materials, methods and examples are merely illustrative and are not intended to be limiting.To the extent not described herein, many details regarding specific materials and processing operations are conventional and can be found in textbooks and other sources within the imprinting and lithography arts.

[0022] As used herein, the terms "comprises," "comprising," "includes," "including," "have," "having," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a process, method, article, or apparatus that includes a list of features is not necessarily limited to only those features and may include other features not expressly described or inherent in such process, method, article, or apparatus.

[0023] As used herein, unless expressly stated to the contrary, "or" refers to inclusive or exclusive or non-inclusive. For example, condition A or B is satisfied by one of: A is true (or present) and B is false (or absent), A is false (or absent) and B is true (or present), or both A and B are true (or present).

[0024] Additionally, the use of "a" or "an" is used to describe elements and components described herein. This is done merely for convenience and to give a general sense of the scope of the invention. This description should be read to include one or at least one, and the singular also includes the plural unless it is clear that it is meant otherwise.

[0025] The present disclosure relates to a curable composition comprising a polymerizable material comprising a first monomer and a second monomer, the second monomer being soluble in the first monomer and comprising a ring structure. In certain embodiments, the ring structure contained in the second monomer can be a maleimide ring, a pyrone ring, or a 2-furanone ring. The curable composition can have a viscosity of 10 mPa·s or less, and can be particularly suitable for use in inkjet adaptive planarization (IAP) to create planar cured layers with fast cure speed, high thermal stability, good mechanical strength, and high etch resistance.

[0026] As used herein, the term monomer refers to one or more polymerizable monomer types. Unless otherwise indicated, the monomer type may be a substituted or unsubstituted monomer.

[0027] In certain embodiments, the second monomer may be a monomer that includes at least one maleimide ring. In one aspect, the second monomer may include one maleimide ring, hereinafter also referred to as a monomaleimide. In yet another aspect, the second monomer may include two maleimide rings, hereinafter also referred to as a bismaleimide. In certain aspects, the maleimide ring may be substituted on the ring nitrogen with an aromatic group. Non-limiting examples of monomaleimides include N-benzylmaleimide (N-BMI) (CAS 1631-26-1); N-cyclohexylmaleimide (N-CMI) (CAS 1631-25-0); N-phenylmaleimide (N-PMI) (CAS 941-69-5); bis(3-ethyl-5-methyl-4-maleimidophenyl)methane (BEMMI) (CAS 105391-33-1); N-(4-nitrophenyl)-maleimide (CAS 4338- 06-1); N-tert-butylmaleimide (CAS 4144-22-3), N-ethyl-maleimide (CAS 128-53-0); N-(2-hydroxyethyl)maleimide (CAS 1585-90-6); N-(2,4,6-trichlorophenyl)maleimide (CAS 13167-25-4); and further non-limiting examples of bismaleimides include bis(3-ethyl-5-methyl-4-maleimidophenyl)methane (BEMMI) (CAS 105391-33-1;1,1'-(methylenedi-4,1-phenylene)bismaleimide (CAS 136760-54-5);1,6-bis-maleimido-hexane (CAS 4856-87-5);1,4-bis-maleimidobutane (CAS 28537-70-4);2,2-bis[4-(4-maleimidophenoxy)phenyl]propane (CAS 79922-55-7);1,8-bis-maleimidotetraethylene glycol (CAS 1 15597-84-7); ethylene-bis-maleimide (CAS 5132-30-9); 1,4-phenylene-bis-maleimide (CAS 3278-31-7); N,N'-(1,3-phenylene)dimaleimide (CAS 2006-93-7); 3-N-maleimidobenzoic acid N-succinimidyl ester (CAS 58626-38-3); or 1,11-bis-maleimidotetraethylene glycol (CAS 86099-06-1).

[0028] The first monomer of the polymerizable material can be present in greater amounts than the second monomer and can dissolve the second monomer. Thus, the first monomer can act as a solvent, and the curable composition can be substantially free of non-polymerizable solvents. However, in another embodiment, the curable composition can also include non-polymerizable solvents.

[0029] In one embodiment, the weight percent ratio of the first monomer to the second monomer can be 3:1 or less, such as 4:1 or less, 5:1 or less, 8:1 or less, 10:1 or less.

[0030] In one embodiment, the first monomer can include at least one acrylate monomer. As used herein, the term acrylate monomer refers to any monomer structure that includes an acrylate or substituted acrylate unit, such as a methacrylate unit. In certain aspects, the acrylate monomer can include an aromatic group. Non-limiting examples of suitable acrylate monomers can be benzyl acrylate (BA); 1-naphthyl acrylate (1-NA); bisphenol A dimethacrylate (BPADMA); or any combination thereof. Other acrylate monomers that can dissolve maleimide-monomers can be, for example, but are not limited to, dicyclopentenyloxyethyl acrylate, dicyclopentanyl acrylate, o-phenylbenzyl acrylate and isobornyl acrylate.

[0031] In another embodiment, the polymerizable material can include at least one additional monomer type, and / or a polymerizable oligomer and / or a polymerizable polymer. In a particular embodiment, the at least one additional monomer can be a difunctional or trifunctional monomer capable of acting as a crosslinker. In one aspect, the at least one additional monomer can be substituted or unsubstituted divinylbenzene (DVB).

[0032] In one particular embodiment, the polymerizable material of the curable composition can include aromatic acrylate monomers, monomers containing a maleimide ring, and substituted or unsubstituted divinylbenzene (DVB).

[0033] An important consideration in the selection of the monomer is the aspect of maintaining a low viscosity of the curable composition before curing. In one embodiment, the viscosity of the curable composition can be 20 mPa·s or less, such as 15 mPa·s or less, 12 mPa·s or less, 10 mPa·s or less, 9 mPa·s or less, or 8 mPa·s or less. In other particular embodiments, the viscosity can be at least 2 mPa·s, such as at least 3 mPa·s, at least 4 mPa·s, or at least 5 mPa·s. In a particularly preferred aspect, the curable composition can have a viscosity of 10 mPa·s or less. As used herein, all viscosity values ​​refer to viscosities measured at a temperature of 23° C. by the Brookfield method using a Brookfield Viscometer at 200 rpm.

[0034] The amount of polymerizable material in the curable composition can be at least 70% by weight, at least 75% by weight, at least 80% by weight, at least 85% by weight, at least 90% by weight, or at least 95% by weight. In another embodiment, the amount of polymerizable material can be 99% by weight or less, for example, 98% by weight or less, 97% by weight or less, 95% by weight or less, 93% by weight or less, 90% by weight or less, or 85% by weight or less, based on the total weight of the curable composition. The amount of polymerizable material can be any value between the above minimum and maximum values. In a particular embodiment, the amount of polymerizable material can be at least 80% by weight and 98% by weight or less.

[0035] The curable composition may further comprise one or more optional additives. Non-limiting examples of the optional additives may be stabilizers, dispersants, solvents, surfactants, inhibitors, or any combination thereof.

[0036] Surprisingly, it has been discovered that by selecting a particular combination of first and second polymerizable monomers, where the second monomer is soluble in the first monomer and contains a maleimide ring, it is possible to create curable compositions that have a desired low viscosity of less than 10 mPa s, and result in cured materials that have low shrinkage during UV curing, excellent mechanical stability, high thermal stability, and good etch resistance.

[0037] In one embodiment, the curable composition can be applied onto a substrate to form a cured layer. Curing can be performed under light irradiation, such as UV radiation, or heat. In this specification, the combination of the substrate and the cured layer covering the substrate is called a laminate.

[0038] In one embodiment, the stiffening layer of the laminate can have a hardness of at least 0.3 GPa, such as at least 0.32 GPa, at least 0.34 GPa, at least 0.36 GPa, or at least 0.38 GPa.

[0039] In another embodiment, the storage modulus of the stiffening layer can be at least 4.5 GPa, e.g., at least 4.6 GPa, at least 4.7 GPa, at least 4.8 GPa, at least 4.9 GPa, at least 5.0 GPa, or at least 5.1.

[0040] The cured layer of the laminate may further have good thermal stability. In one embodiment, the photocured layer may have a weight loss of 4% or less, 3.5% or less, 3% or less, 2.7% or less, 2.5% or less, 2.3% or less, 2.0% or less, or 1.7% or less after heat treatment at 250° C. for 90 seconds.

[0041] The cured layer of the laminate of the present disclosure can have a high carbon content. In one embodiment, the carbon content of the cured layer can be at least 70 wt%, for example, at least 71 wt%, at least 72 wt%, at least 73 wt%, at least 74 wt%, or at least 75 wt%, based on the total weight of the cured layer. In a particular aspect, the carbon content can be at least 74 wt%.

[0042] In another embodiment, the cured layer of the laminate may have a hydrogen content of 6.3 wt.% or less, e.g., 6.2 wt.% or less, 6.1 wt.% or less, or 6.0 wt.% or less, based on the total weight of the cured layer.

[0043] In yet another embodiment, the glass transition temperature of the cured layer of the laminate can be at least 80°C, such as at least 85°C, at least 90°C, at least 100°C, at least 110°C, or at least 115°C.

[0044] In one embodiment, the stiffening layer of the laminate can have an Ohnishi number of 3.0 or less, such as 2.9 or less, 2.8 or less, 2.7 or less, 2.65 or less, or 2.6 or less. In another embodiment, the Ohnishi number can be at least 1.8, e.g., at least 1.9, at least 2.0, at least 2.1, at least 2.2, or at least 2.3.

[0045] The present disclosure is further directed to a method of forming a cured layer, which may include applying a layer of the above-described curable composition onto a substrate, contacting the curable composition with a superstrate or curing the curable composition with heat to form a cured layer, and removing the superstrate from the cured layer.

[0046] More surprisingly, it has been observed that the curing of the curable composition of the present disclosure requires a very short curing time.In one embodiment, at least 65% of all C=C double bonds contained in the polymerizable material can be converted within 10 seconds of UV irradiation time.In other aspects, the C=C conversion after 10 seconds of curing under UV irradiation can be at least 70%, for example at least 75%, at least 80%, at least 85%, or at least 90%, based on the total amount of C=C double bonds contained in the polymerizable material.

[0047] In another embodiment, at least 80% of all double bonds of the polymerizable material, for example, at least 85%, at least 90%, at least 95%, or at least 98%, based on the total amount of C=C double bonds contained in the polymerizable material of the composition, may be converted after 100 seconds of curing under UV irradiation.

[0048] The substrate and solidified (cured) layer can undergo additional processing to form the desired article, which can include, for example, an etching process to transfer an image into the substrate that corresponds to a pattern in one or both of the solidified layer and / or the patterned layer underlying the solidified layer. The substrate can be further subjected to known steps and processes for device (article) manufacturing, including, for example, curing, oxidation, layering, deposition, doping, planarization, etching, removal of formable material, dicing, bonding, packaging, etc. In some embodiments, the substrate can be processed to manufacture multiple articles (devices).

[0049] The hardened layer may be further used as an interlayer insulating film or a resist film for semiconductor devices such as LSI, system LSI, DRAM, SDRAM, RDRAM, and D-RDRAM used in the semiconductor manufacturing process.

[0050] As further shown in the examples, it has been surprisingly discovered that certain combinations of aromatic group-containing polymerizable monomers in a curable composition have properties that are particularly well suited for IAP processing. The curable compositions of the present disclosure can have a desirable low viscosity of 10 mPa·s or less and can form cured layers having high mechanical strength, high thermal stability and low shrinkage. EXAMPLES

[0051] The following non-limiting examples illustrate the concepts described herein.

[0052] Example 1

[0053] Preparation of Photocurable IAP Compositions.

[0054] Six photocurable compositions (samples S1 to S6) were prepared by combining 50% by weight of benzyl acrylate (BA) as the first monomer and 10% by weight of a monomer containing a maleimide ring substituted with an aromatic at the N-position as the second monomer for each composition. The monomer containing a maleimide ring was selected from N-benzylmaleimide (N-BMI), N-cyclohexylmaleimide (N-CMI), N-phenylmaleimide (N-PMI), and bis(3-ethyl-5-methyl-4-maleimidophenyl)methane (BEMMI). Each composition further contained 20% by weight of naphthyl acrylate (NA), and one or two other polymerizable monomers selected from divinylbenzene (DVB) and bisphenyl A dimethacrylate (BPADMA). Additionally, each composition contained 3 wt. % Irgacure 819 (from LabNetworks) and 1 wt. % of the surfactant Chemguard S554 (from Chemguard), based on the total weight of the composition.

[0055] A summary of the types and amounts of polymerizable monomers included in the compositions of Samples S1-S6 is provided in Table 1. All weight percent amounts of monomers listed in Table 1 are based on 100 weight percent of the total amount of polymerizable material, meaning that the amounts of monomers listed for each composition listed in Table 1 add up to 100 weight percent.

[0056] Table 1 further includes the carbon content, hydrogen content, and Ohnishi number of the compositions. The Ohnishi number (ON) is an empirical parameter, calculated as the ratio of the total number of atoms in a polymer repeat unit (Nt) divided by the difference between the number of carbon atoms (Nc) and the number of oxygen atoms (No) in the unit, ON=Nt / (Nc-No). For the calculation of the Ohnishi number, it was assumed that there was no loss of atoms during polymerization and that the cured material contained 100% by weight of the added polymerized monomer units.

[0057] [Table 1]

[0058] Table 1 also includes a comparative sample C1, which does not contain any maleimide monomers in the polymerizable material and is a commercially available IAP resist material.

[0059] Other tested properties of samples S1-S6 and C1, such as viscosity, UV shrinkage during curing, and glass transition temperature Tg after curing, are summarized in Table 2. Curing was performed by applying a liquid film of the photocurable composition to a glass substrate with a thickness of about 100 nm, followed by exposure to UV light with an intensity of 4 mW / cm. 2 for 600 seconds, which resulted in a curing energy of 2.4 J / cm 2 is equivalent to.

[0060] Table 2 further includes data on the weight loss of the samples at 250°C for some samples to simulate the wafer baking process. Thermogravimetric analysis (TGA) was performed by heating at a rate of 20°C per minute to 250°C, holding at this temperature for 90 seconds, and measuring the weight loss. Surprisingly, it was observed that samples S4, S5, and S6 all lost less than 3% weight after heating. The weight loss of sample S6 was particularly low at only 1.34%. Without being bound by theory, the weight loss during the heat treatment of the samples at 250°C may indicate that a greater degree of monomer was polymerized in samples with lower weight loss, e.g., sample S6, than in samples with higher weight loss, e.g., sample S4.

[0061] [Table 2]

[0062] The viscosity of the samples was measured at 23°C using a Brookfield Viscometer LVDV-II+Pro at 200 rpm with spindle size #18. For the viscosity tests, approximately 6-7 mL of sample liquid was added to the sample chamber, enough to cover the spindle head. For all viscosity tests, at least three measurements were taken and the average value was calculated.

[0063] UV shrinkage measurements were performed using an Anton Paar MCR-301 rheometer coupled to a UV curing system and heater. For the test, a 7 μL droplet of the test sample was added onto the plate, and the temperature-controlled hood was opened to insulate the droplet and the measurement unit. The amount of sample was designed such that the thickness (hereafter also referred to as "height") of the sample layer was slightly higher than 0.1 mm. When the target height was set to 0.1 mm, the measurement unit moved below the set value, causing the excess amount of resist to flow out of the plate. This ensured that the exact height of the liquid resist before curing was 0.1 mm. The resist was then heated to 4 mW / cm. 2 The resist was cured at 365 nm for 600 s with a UV power of 1000 Hz. After the resist was cured, the height was measured again and the linear shrinkage was calculated according to equation (1). SL=(L R -L CR / L R )×100%(1) (In the formula, L R is the thickness of the photocurable composition layer before curing, and L CR is the thickness of the cured photocurable composition layer).

[0064] Example 2

[0065] The storage modulus and hardness of photocured samples S2, S5 and S6 described in Example 1 were measured and compared to comparative sample C2.

[0066] Comparative sample C2 was a typical resist material for nanoimprint lithography (NIL). C2 contained the following materials: 33.3 wt% isobornyl acrylate (IBOA), 19.4 wt% dicyclopentyl acrylate (DCPA), 22.2 wt% BA, 18.5 wt% neopentyl glycol diacrylate (A-NPG), 0.925 wt% and 1.85% photoinitiators Irgacure 907 and Irgacure 651, respectively, and 3.79 wt% surfactant. Comparative sample C2 had a viscosity of 6.8 mPa·s, a UV shrinkage during curing of 4.5%, a carbon content of 71%, a glass transition temperature of 90°C, and an Ohnishi number of 3.26.

[0067] A summary of the test results is shown in Table 3. The test results showed that samples S2, S5, and S6 all had higher storage modulus and hardness than comparative sample C2. The highest storage modulus was achieved with sample S6, a difunctional maleimide monomer (containing two maleimide rings).

[0068] Baking (heat treatment at 250 °C for 2 min prior to indentation testing) had little effect on the compositions containing maleimide monomers (samples S2, S5, and S6), but the hardness of comparative sample C2 increased after baking, reaching a value close to that of sample S6.

[0069] [Table 3]

[0070] The storage modulus and glass transition temperature were measured with an Anton-Paar MCR-301 rheometer coupled with a Hamamatsu Lightningcure LC8 UV source. The samples were exposed to 1.0 mW / cm at 365 nm controlled by a Hamamatsu 365 nm UV power meter. 2 The rheometer was irradiated with a UV intensity of 1000 nm. A software named RheoPlus was used to control the rheometer and perform data analysis. The temperature was controlled by a Julabo F25-ME water unit and was set at 23 °C as the starting temperature. For each sample test, 7 μl of resist sample was added onto the glass plate located directly under the measurement system of the rheometer. Before starting the UV exposure, the distance between the glass plate and the measurement unit was reduced to a gap of 0.1 mm. The UV exposure was continued until the storage modulus reached a plateau, and the height of the plateau was recorded as the storage modulus shown in Table 3.

[0071] After UV curing was completed, the temperature of the cured sample was increased by controlled heating, and the temperature-dependent change in storage modulus was measured to obtain the glass transition temperature, Tg, which was considered to be the temperature corresponding to the maximum value of Tangent(θ).

[0072] Hardness was calculated from the load curves measured with a Hysitron TI950 Triboindenter with indentations up to 200 nm using a displacement controlled loading function. The force was measured during the indentation, from which the load curve was obtained. Hardness (H) was calculated according to the following formula: H=P max / A c (Here, P max is the maximum load, and A c is the contact area determined by the tip area function). It was calculated by:

[0073] Example 3

[0074] Double bond transformation studies

[0075] Fourier transform infrared spectroscopy (FTIR) was performed to monitor the real-time UV curing kinetics of samples S1 to S6 described in Example 1. -1 The decrease in the peak of the double bond C=C in the IR spectrum at 100 s was observed in real time after the start of the curing reaction. The applied UV light intensity was 4 mW / cm for a time of 100 s. 2 ,30mW / cm 2 As shown in Figure 1, 2 or 30mW / cm 2 No difference was observed in double bond conversion after 100 seconds when a light intensity of 0.01 was applied.

[0076] Furthermore, in all samples S1-S6, most of the double bond conversion occurred within a very short time, such as the first 10 seconds, after the initiation of the polymerization reaction by UV irradiation, as shown in Figure 2. In Figure 2, the initiation of UV radiation began at a time of 10 seconds, proceeded for a time of 100 seconds, and ended at a time of 110 seconds on the x-axis.

[0077] The highest double bond conversion (close to 100%) was reached for sample S6, which contained a difunctional maleimide monomer. However, samples S2–S5 (containing monofunctional maleimide monomers) also reached high conversions of 82.8%–92.4% after 100 s curing.

[0078] Table 4 below shows the percentage of double bonds returned for each test sample at 10 seconds and 100 seconds.

[0079] [Table 4]

[0080] The specification and figures of the embodiments described herein are intended to provide a general understanding of the structure of the various embodiments. The specification and figures are not intended to be an exhaustive and comprehensive description of all elements and features of the apparatus and systems that use the structures or methods described herein. Separate embodiments may also be provided in combination in a single embodiment, and conversely, various features that are described for brevity in the context of a single embodiment may be provided separately or in any subcombination. Furthermore, references to values ​​described in ranges include each value within that range. Many other embodiments will be apparent to those skilled in the art only upon reading this specification. Other embodiments may be used and derived from the present disclosure, such that structural substitutions, logical substitutions, or other changes may be made without departing from the scope of the present disclosure. Thus, the present disclosure should be considered illustrative and not limiting.

Claims

1. 1. A curable composition comprising a polymerizable material and an initiator, the polymerizable material comprises a first monomer, a second monomer, and substituted or unsubstituted divinylbenzene (DVB); the second monomer comprises a ring structure selected from a maleimide ring, a pyrone ring, or a 2-furanone ring; the second monomer is soluble in the first monomer; having a viscosity of 10 mPa·s or less at 23° C. and 200 rpm; the amount of polymerizable material in the curable composition is 70 to 99 wt. %; The amount of the second monomer is 2% by weight or more and 20% by weight or less, based on the total weight of the curable composition; Curable composition.

2. The curable composition of claim 1 , wherein the second monomer comprises a maleimide ring structure.

3. 3. The curable composition of claim 2, wherein the second monomer comprises N-benzylmaleimide (N-BMI), N-cyclohexylmaleimide (N-CMI), N-phenylmaleimide (N-PMI), bis(3-ethyl-5-methyl-4-maleimidophenyl)methane (BEMMI), or any combination thereof.

4. The curable composition of claim 1 , wherein the first monomer comprises an acrylate monomer.

5. The curable composition of claim 4 wherein the acrylate monomer comprises an aromatic group.

6. The curable composition of claim 5, wherein the acrylate monomer comprises benzyl acrylate (BA), 1-naphthyl acrylate (1-NA), bisphenol A dimethacrylate (BPADMA), or any combination thereof.

7. 1. A curable composition comprising a polymerizable material and an initiator, the polymerizable material comprises a first monomer and a second monomer; the second monomer comprises a ring structure selected from a maleimide ring, a pyrone ring, or a 2-furanone ring; the second monomer is soluble in the first monomer; having a viscosity of 10 mPa·s or less at 23° C. and 200 rpm; the first monomer comprises an acrylate monomer comprising an aromatic group; at least 80 wt. % of said polymerizable material based on the total weight of said curable composition; The curable composition has a total carbon content of 74% or more after curing. Curable composition.

8. 8. The curable composition of claim 7, wherein the amount of the second monomer is from 2 wt% to 20 wt%, based on the total weight of the curable composition.

9. The curable composition of claim 8, wherein the polymerizable material comprises at least one additional monomer.

10. 10. The curable composition of claim 9, wherein the at least one additional monomer comprises a substituted or unsubstituted divinylbenzene (DVB).

11. 11. The curable composition of claim 1, wherein the polymerizable material comprises an aromatic acrylate monomer, a monomer containing a maleimide ring, and a substituted or unsubstituted divinylbenzene (DVB).

12. 12. The curable composition of claim 1, wherein the curable composition is free of non-polymerizable solvents.

13. 13. A laminate comprising a substrate and a cured layer covering the substrate, the cured layer being obtained from a curable composition according to any one of claims 1 to 12, the cured layer having a total carbon content of 74% or more, and a weight loss of the cured layer after heat treatment at a temperature of 250°C for 90 seconds of 2.5% or less relative to the total weight of the cured layer before said heat treatment.

14. 14. The laminate of claim 13, wherein the stiffening layer has a storage modulus of at least 4.5 GPa.

15. A method of making an article comprising: applying a layer of a curable composition onto a substrate, wherein the curable composition comprises a polymerizable material and a photoinitiator, the polymerizable material comprises a first monomer, a second monomer, and substituted or unsubstituted divinylbenzene (DVB), the second monomer comprises a ring structure selected from a maleimide ring, a pyrone ring, or a 2-furanone ring, and the second monomer is soluble in the first monomer; the viscosity of the curable composition is 10 mPa·s or less at 23° C. and 200 rpm, and the amount of polymerizable material in the curable composition is 70 to 99 wt %; The amount of the second monomer is 2% by weight or more and 20% by weight or less, based on the total weight of the curable composition; contacting the curable composition with a superstrate; curing the curable composition with light or heat to form a cured layer; removing the superstrate from the hardened layer; and Treating the substrate with the cured layer to produce the article.

16. A method of making an article comprising: applying a layer of a curable composition onto a substrate, wherein the curable composition comprises a polymerizable material and a photoinitiator, the polymerizable material comprises a first monomer and a second monomer, the second monomer comprises a ring structure selected from a maleimide ring, a pyrone ring, or a 2-furanone ring, and the second monomer is soluble in the first monomer; The viscosity of the curable composition is 10 mPa·s or less at 23° C. and 200 rpm; the first monomer comprises an acrylate monomer comprising an aromatic group; at least 80 wt. % of said polymerizable material based on the total weight of said curable composition; The total carbon content of the curable composition after curing is 74% or more. contacting the curable composition with a superstrate; curing the curable composition with light or heat to form a cured layer; removing the superstrate from the hardened layer; and Treating the substrate with the cured layer to produce the article.

17. 17. The method of claim 15 or 16, wherein curing involves conversion of at least 65% of all double bonds contained in the polymerizable material within 10 seconds.

18. 17. The method of claim 15 or 16, wherein the polymerizable material comprises an acrylate monomer as the first monomer and a monomer containing a maleimide ring as the second monomer.

19. The method of claim 16 , wherein the polymerizable material comprises at least one additional monomer.

20. 20. The method of claim 19, wherein the at least one additional monomer is a substituted or unsubstituted divinylbenzene.

21. 17. The method of claim 15 or 16, wherein the cured layer has a weight loss after heat treatment at a temperature of 250°C for 90 seconds of 2.5% or less of the total weight of the cured layer.

Citation Information

Patent Citations

  • Polymerizable composition

    JP2011057751A

  • Curable resin composition for inkjet, cured product thereof and printed wiring board having the cured product

    JP2012214532A

  • Cured film

    JP2014177505A

  • Method for manufacturing 3D shaped object, photocurable composition for 3D shaping, and ink set for 3D shaping

    JP2016002683A

  • Ink composition for inkjet recording and inkjet recording method

    JP2016160334A